Temperature and heat flux measurement techniques for aeroengine fire test: a review - Mohammed, I.; Abu Talib, A. R.; H. Sultan, M. T.; Saadon, S. (Institute of Physics Publishing, 2016)
This review is made of studies whereby some types of fire test measuring instrument were compared based on their mode of operation, sensing ability, temperature resistance and their calibration mode used for aero-engine applications. The study discusses issues affecting temperature and heat flux measurement, methods of measurement, calibration and uncertainties that occur in the fire test. It is found that the temperature and heat flux measurements of the flame from the standard burner need to be corrected and taken into account for radiation heat loss. Methods for temperature and heat flux measurements, as well as uncertainties analysis, were also discussed.